Habilidades sociales y asertividad en estudiantes de secundaria del área de Ciencias Sociales en la I.E.P.S.M. N°60259 Señor de los Milagros San Antonio, distrito de San Pablo 2023 - Lopez Pastrana, Oses Jose (2024)
The study focused on examining the relationship between the level of social skills and assertiveness in secondary school students in the Social Sciences area at I.E.P.S.M. No. 60259 in San Antonio, located in San Pablo, during 2023. A non experimental, cross-sectional, field-based, bivariate, and relational design methodology was used. The sample consisted of 89 students who completed surveys through previously validated questionnaires. The study achieved its objective, revealing a moderate positive correlation (rho = 0.413, p < 0.05) between social skills and assertiveness. These results suggest that a higher level of social skills is associated with greater assertiveness. Most students exhibited acceptable to good levels in both dimensions, highlighting the importance of developing social skills to enhance assertiveness in the educational context.